An Indian Residential School survivor's journey with Truth and Reconciliation - Conrad, Arlene Shirley (2019)
As an Indigenous woman and an Indian Residential School survivor, I embark on a journey that forms a roadmap of my life experiences that are part of the history of Canada. I share who I am and how I self-identify as someone born of mixed ancestry. I share stories of my Dene culture and the experience that my siblings and I had while at Indian Residential School (IRS). The question, “What is my truth and reconciliation?” opens up an array of interpretations and subsequent questions that reference many aspects of my political and cultural viewpoints. I use a blended qualitative research approach using Indigenous research methodology and autoethnography to explore Indigenous cultural ideologies to interpret reconciliation. Data was collected through a set of questions in a guided focus group with my two siblings. The focus group questions brought out thoughts, feelings, and emotions from IRS that resonated around childhood trauma. Through thematic analysis, I discovered similarities in our answers and together we gained a deeper understanding of our childhood trauma as experienced at IRS. I bridge the gap between the past and the present as I acknowledge my lived realities that enable me to move beyond personal trauma to healing in the form of decolonization and reconciliation. In my Indigenous world today those two words serve as a bridge towards my healing journey. Keywords: healing, trauma, reconciliation, decolonization, separation, memory, survivor